Shu’ûbât Ta’lîm At-Ta’bîr At-Tahrîriy ladâ Thâlibât Al-I’dâd Al-Lughawiy bi Jâmi’ati Ar-Râyah fî Sukabumi - Mukhlishoh Mukhlishoh; Arini El-Haq; Abdul Aziz; Muhammad Khanif; Nur Cholis Slamet Ramlan (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
Mastery of essay written is mastery of Arabic entirely, because in it there is the application of elements of Arabic, especially vocabulary and compositions. This study aims to: 1) Knowing the types of difficulties or problems faced by Language Preparation Female Students Ar- Raayah University in learning essay written. 2) Reveal the cause of the problem to get a solution from the cause. 3) Reveal the effect of these difficulties in learning essay written. The method used in this research is a case study method through a qualitative approach, and the data collected is analyzed by various methods, namely interviews, observation, sorting, presenting and drawing conclusions. The results of the study were: 1) The types of difficulties faced by Language Preparation Female Students Ar- Raayah University in learning essay written were some of them faced difficulties in expressing what came to mind into writing, difficulties in connecting ideas, and difficulty in selecting some vocabulary, difficulty in applying grammar and spelling. 2) The causes of difficulties in learning essay written are due to a lack of understanding of the text, a lack of linguistic balance, and the influence of the mother tongue and the language of the environment. 3) Difficulty learning essay written affects academic achievement, writing academic research, and the existence of negative behavior about essay written. The conclusion of the study shows the importance of eliminating these difficulties by overcoming their causes to assist female students in learning Essay Written in improving academic achievement, writing good academic research, and avoiding negative behaviors from learning essay written. Keywords: Difficulty, Learning, Essay Written, Arabic, STIBA Ar-Raayah